New fertile isidiate Graphidaceae from the Solomon Islands - Aptroot, André (Phytotaxa, 2014)
Two new species of Graphidaceae are described from the Solomon Islands. Fissurina longiisidiata occurs on tree bark in lowland forests and is characterized by the presence of long cylindrical, glossy green isidia and 3-septate ascospores. Pseudoramonia isidiata occurs on dead leaves in mountain forest and is characterized by the presence of gnarled, somewhat tapering, whitish grey isidia and 7-septate, somewhat clavate ascospores.